Strategi Aktivisme Digital #MeToo Movement di Amerika Serikat - Farah Liana Ismahani; Najamuddin Khairur Rijal; Muhammad Fadzryl Adzmy (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
The presence of the #MeToo movement is an early sign of a social movement through social networks in voicing injustice over sexual cases that occur in the workplace in the United States. This reseach aims to explain the strategy of the digital campaign of the #MeToo movement as a movement to fight for the rights of victims of sexual cases by using qualitative research methods with the concept of Online Social Movement and Digital Activism. The results of this study indicate that the sustainability of the digital campaign of the #MeToo movement uses a strategy from digital activism which includes accessibility, namely the #MeToo movement chooses a modern campaign method by using social media such as twitter, instagram, facebook, and myspace. Then look at the popularity, namely by using the hashtag #MeToo as a frame of movement that is easy to share on social media. Finally, the ecosystem, the outbreak of the #MeToo movement has received positive responses from victims and the community thus driving a number of transformations.